Strategy
Strategic execution drives business success. This book covers strategy from the ground up, explaining what strategy is, how to put together a strategic plan, what tools and resources are necessary to execute it, and how to measure results. The Harvard Business Essentials series is designed to provide comprehensive advice, personal coaching, background information, and guidance on the most relevant topics in business. Whether you are a new manager seeking to expand your skills or a seasoned professional looking to broaden your knowledge base, these solution-oriented books put reliable answers at your fingertips